Results of WICOVIR Gargle Pool PCR Testing in German Schools Based on the First 100,000 Tests - Kheiroddin, Parastoo; Schöberl, Patricia; Althammer, Michael; Cibali, Ezgi; Würfel, Thea; Wein, Hannah; Kulawik, Birgit; Buntrock-Döpke, Heike; Weigl, Eva; Gran, Silvia; Gründl, Magdalena; Langguth, Jana; et al. (Frontiers in Pediatrics, 2021)
Background: Opening schools and keeping children safe from SARS-CoV-2 infections at the same time is urgently needed to protect children from direct and indirect consequences of the COVID19 pandemic. To achieve this goal, a safe, efficient, and cost-effective SARS-CoV-2 testing system for schools is necessary. Methods: We implemented the screening WICOVIR concept for schools in the southeast of Germany, which is based on gargling at home, pooling of samples in schools and assessment of SARS-CoV-2 by pool rRT-PCR, performed decentralized in numerous participating laborato-ries. Depooling was performed if pools were positive and results were transmitted with soft-ware specifically developed for the project within a day. Findings: We developed and implemented the proof-of-concept test system within a pilot phase of 5 weeks based on almost 17.000 participants. After 6 weeks in the main phase of the project, we have performed >100,000 tests in total analyzed in 7896 pools, identifying 19 cases in >100 participating schools. On average, positive children show an individual CT value of 31 when identified in the pools. Up to 30 samples were pooled (mean 13), in general based on school classes and attached schools staff. All three participating laboratories detected positive samples reliably with their previously established rRT-PCR standard protocols. When self-administered antigen-tests were performed concomitantly in positive cases, only one of these eight tests was positive and when also antigen tests performed after positive pool rRT-PCR results were al-ready known are included, 3 out of 11 truly positive tests were also identified by antigen testing. After 3 weeks of repetitive WICOVIR testing twice weekly, the detection rate of positive chil-dren in that cohort decreased significantly from 0·042 to 0·012 (p=0·008). Interpretation: Repeated gargle pool rRT-PCR testing can be implemented quickly in schools. It is an effective, valid, and well received test system for schools, superior to antigen tests in sensitivity, acceptance, and costs.